Práticas de observação astronômica no ensino médio: uma proposta de sequência didática para uso de telescópio remoto - Lyra, Victor Souza (2020)
This work deals with the elaboration and implementation of an educational product in the form of a Didactic Sequence (DS) for high school students and aims to use a remote telescope to trace a historical path, starting from the simple observation of the sky with the naked eye and achieve remote observation through a telescope. It is understood that work like this is important because, in the school environment, greater emphasis is placed on the basic understanding of scientific terms and concepts, leaving in the background the issue of understanding the nature of Science and its relationship with technology and the society. The DS takes the history and epistemology of Science as its guiding axis and will involve the topic of astronomical observations. Students interested in participating took a course of 10 expository classes dialogued, with the possibility of making astronomical observations with the naked eye and using some instruments and telescopes. The purpose of the course was to offer the students involved a vision of how science thinking and doing go hand in hand with their historical and cultural contexts, relating what was observed in the sky to the way of seeing the world at different times. Concepts of the history and epistemology of Science were explored as a guiding principle for the development of DS. Using Gowin's “V” in an inductive perspective, DS analysis was performed to validate it, as well as redesign completing the first cycle of the iterative process of the Teaching and Learning Sequence (TLS). From the comments and questions made by the students during the course, transcribed in this work, it was possible to characterize the occurrence of elements of the history and epistemology of Science during the DS.